PEMBUATAN KAMPAS KOPLING MENGGUNAKAN SERAT SERABUT KELAPA - Junaidi Junaidi; Fadly Ahmad Kurniawan Nasution (Jurnal Simetri Rekayasa, 2021)
In this study, the authors tried to develop clutch lining products made from non-asbestos, because the raw material for coconut fiber in Indonesia is very abundant. Indonesian coconut production averages 15.5 billion eggs/year or equivalent to 3.02 million tonnes of copra, 3.75 million tonnes of water, 0.75 million tonnes of shell charcoal, 1.8 million tonnes of coir fiber and 3.3 million tonnes of methamphetamine dust. Knowing the wear rate of clutch linings using coconut fiber. Knowing the comparison of the quality of clutch linings made from asbestos with clutch linings made from coconut fiber and a mixture of fiberglass fibers. for the type of coupling pads specimen 1 has superior quality compared to standard commercial clutch pads, of the 2 types of clutch pads mixed from coconut fiber, specimen 1 is superior to specimen 2 this is because the friction temperature that occurs is lower compared to commercial clutch pads and clutch pads specimen 2. Clutch lining made of asbestos has a max Temperature value of: 415°C Total final thickness: 3mm Total final weight: 9g, Clutch lining made of coconut fiber fiber (specimen 1) has a max Temperature value of: 331°C Total final thickness: 4, 7mm Total final weight: 10g, Coupling lining made from coconut fiber (specimen 2) has a max. Temprature value: 372°C Total final thickness: 4.1mm Total final weight: 15g